Can Rehabilitation Work in Military Prison? A Theoretical Framework Based on the Israeli Case - Itzik, Lea (The prison journal, 2023)
Israel's military prisons operate a rehabilitation program for imprisoned soldiers based on a psychosocial diagnosis. The program's essential aim is to help soldiers complete their service and avoid re-incarceration. This article describes the program, its function related to the integrative law court, and its role as the army's probation service. It further presents a unique perspective regarding military rehabilitation programs, demonstrating how rehabilitation leads to recidivism. It concludes with a recommendation for incorporating an organizational change in the program that involves redistributing the existing sections to operate under two different authorities.